Seasonal dynamics of total flavonoid contents and antioxidant activity of Dryopteris erythrosora. (1st November 2015) - Xie, Yinghua; Zheng, Yunxia; Dai, Xiling; Wang, Quanxi; Cao, Jianguo; Xiao, Jianbo
Highlights: The total flavonoids content in various parts of D. erythrosora obviously appear an obvious seasonal dynamic change. The total flavonoids content in the stems show a negative correlation with that in the leaves. The total flavonoids content in stems is much higher than that in the roots, rachis and leaves. The antioxidant activities of the extracts also altered in proportion to the change of total flavonoid contents. The extracts from stems always showed highest antioxidant potentials. Abstract: The seasonal dynamics of the total flavonoid contents in various parts of Dryopteris erythrosora, a traditional Chinese medicinal fern, and their antioxidant activity were investigated. The total flavonoids content in various parts of D. erythrosora showed an obvious seasonal dynamic change. The total flavonoid contents in stems (from 4.3% to 12.5%) were much higher than that in leaves with an average content of 2.01%. In spring, the total flavonoid contents in stems were relatively low, but increased rapidly from summer to winter. However, the seasonal dynamics of total flavonoid contents in leaves showed different model. The total flavonoid contents in the stems showed a negative correlation with that in the leaves from January to July. The correlation coefficient of about −0.7 was obtained. The antioxidant activity of the extracts also altered in proportion to the change of total flavonoid contents. In general, the extracts from stems always showed highest antioxidant potentials and it was suggested that the stems can be used as crude medicine.